Aqueous extracts of the leaves of Sesbania sesban reduces development of diabetic nephropathy in streptozotocin-induced diabetic rat - Ramdas Bhanudas Pandhare; B. Sangameswaran; Popat B. Mohite; Shantaram G. Khanage (Bangladesh Pharmacological Society, 2011)
The renal protective effect of the aqueous extract of Sesbania sesban leaves (250 and 500 mg/kg/day) in streptozotocin-induced diabetic rats were studied. Diabetic rats showed severe hyperglycemia with marked increase in proteinuria and albuminuria. Thye aqueous extract reduced proteinuria, albuminuria, lipid and glycated hemoglobin (HbA1c) deposition in diabetic rats. Histopathology studies on kidneys of diabetic rats revealed severe increase in mesangial cells and matrix of glomeruli with hyaline thickening of some arteriole wall, resulted from selective albuminuria and proteinuria. These changes are inhibited by the extract and glibenclamide. These results suggested that aqueous extract of S. sesban has reduced development of diabetic nephropathy in streptozotocin-induced diabetic rats.